Disability and Popular Culture Focusing Passion, Creating Community and Expressing Defiance - Ellis, Katie (Ashgate Publishing, Ltd., 2015)
Drawing on central theoretical approaches in the field of critical disability studies, this book examines disability across a number of internationally recognised texts and objects.